Shrimp aquaculture in the federal state of Ceará, 1970–2012: trends after mangrove forest privatization in Brazil - Queiroz, L. (2023)
During the last 40 years, industrial shrimp farming in Brazil has experienced intense development. The first shrimp culture experiments were carried out at the beginning of the 1970s, but due to technical problems and a lack of exact knowledge they were not very successful. At the end of the 1990s, the activity expanded rapidly and shrimp farming became a relevant export industry, due to government assistance, public-bank financing, university technical collaboration and legislative permissiveness. The vertiginous growth of the industry has been accompanied by a profound transformation of natural resources, causing the degradation of the mangrove ecosystem. The objective of this study is to conduct an integral and in-depth analysis of the evolution of the industrial shrimp farming in Brazil, based on a review of the national political and economic context of the aquaculture activity, and also an evaluation of the environmental impacts of shrimp farming in the watershed of the Jaguaribe River, Ceará (NE Brazil). This analysis begins with the initiation of intensive large-scale farming for export, taking into account the synthesis of environmental processes to analyse the socio-environmental impacts. We studied the areas used for the construction of shrimp farms, located in coastal and estuarine systems and with tidal connections, linking the transformation of the system with the, geo-environmental evolution of the impacted zones, mainly the mangrove ecosystem. The final objective of this work is to propose an integral model of management for the appropriate use of mangroves in Brazil and other systems with analogous problems.